2014
DOI: 10.1073/pnas.1405768111
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of a voltage-gated Na+channel by sevoflurane involves multiple sites and distinct mechanisms

Abstract: Halogenated inhaled general anesthetic agents modulate voltagegated ion channels, but the underlying molecular mechanisms are not understood. Many general anesthetic agents regulate voltagegated Na + (Na V ) channels, including the commonly used drug sevoflurane. Here, we investigated the putative binding sites and molecular mechanisms of sevoflurane action on the bacterial Na V channel NaChBac by using a combination of molecular dynamics simulation, electrophysiology, and kinetic analysis. Structural modeling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
96
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(107 citation statements)
references
References 53 publications
10
96
1
Order By: Relevance
“…A completely converged average over this degree of freedom cannot be assumed. At other sites, such as in the central pore cavity, anesthetics showed a rather fast rotational tumbling and translational diffusivity in the simulation (11). Such extreme mobility might reduce the cross-relaxation rate, rendering binding undetectable by STD.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…A completely converged average over this degree of freedom cannot be assumed. At other sites, such as in the central pore cavity, anesthetics showed a rather fast rotational tumbling and translational diffusivity in the simulation (11). Such extreme mobility might reduce the cross-relaxation rate, rendering binding undetectable by STD.…”
Section: Discussionmentioning
confidence: 95%
“…This method depends critically on the availability of a reliable structural model, either from experimental structures or from homology modeling. The success in the strategic placement of 19 F probes based on the predictions of potential isoflurane binding sites from MD simulations (11,12) underscores the power of combining experimental NMR with computational simulations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Na v Bac family lacks the Domain (D) III-DIV linker responsible for fast inactivation (3), enabling molecular-level investigation into this common modulation process. Moreover, key binding regions are well conserved in bacterial and mammalian channels (3,11), and it has been shown that bacterial channels interact with common inhibitory drugs (11)(12)(13)(14). However, questions remain as to how structurally disparate inhibitor molecules can cause qualitatively similar modulation of different mammalian and bacterial Na v channels.…”
mentioning
confidence: 99%
“…Another MD flooding simulation and combined electrophysiology study of NaChBac interactions revealed that sevoflurane, at low (0.2 mM) and high (2.0 mM) concentrations, shifted both the voltage-dependence of activation and inactivation toward more hyperpolarized potentials. However, in contrast to the effects of isoflurane, peak Na + current was potentiated at the low sevoflurane concentration, and there was an increase in the rate constant for recovery from inactivation (Barber et al 2014). This acceleration is in contrast to the electrophysiological effects of volatile anesthetics on NaChBac and mammalian Na v , where recovery from inactivation is prolonged (Ouyang et al 2007; Ouyang et al 2009; Herold et al 2014; Purtell et al 2015).…”
Section: Identification Of Anesthetic Binding Sites Within Prokaryotimentioning
confidence: 99%